Mga Beki sa Pinilakang Tabing a descriptive analysis on the portrayals of Gay characters in Philippine cinema starting 1954 to 2015 - Incensario, Cindy I.; Lebuna, Marianne Lou D.; Zalavarria, Zarahbell Ann O. (2016.)
This research study examine the portrayal of gay characters in the Philippine cinema over a seven decade period, focusing on the gay character?s verbal, visual, and performance elements and the film?s genre. A qualitative content analysis was conducted on nine-themed films: Jack en Jill (1959), Facifica Falayfay (1969), Ang Tatay Kong Nanay (1978), Manila by Night (1980), Pusong Mamon (1998), Ang Pagdadalaga ni Maximo Oliveros (2003), In My Life (2009), Bwakaw (2012), and Beauty and the Bestie (2015). The researchers were able to identify two main types of gay portrayals: effeminate and masculine gay. Effeminate gay characters re either classified as the screaming transvestite or the parloristang bakla. Earlier films focused on the bakla image, that of a man who wants to be a woman and tries to transform himself by looking and acting feminine. It showed a shallow understanding of homosexuality and shield away from confronting issues such as the bakla male?s sexual preferences. Later films became more daring and showed images of gay men who did not feel the need or desire to become female but were attracted to other males or to both sexes. Other films explored deeper issues such as identity crisis, issues of social acceptance, tolerance and discrimination, same sex coupling and cohabitation, and the desire to have children or raise a family. The study concludes that despite the emergence of the masculine portrayal in the 20th century and the noteworthy acceptance of the Filipino audience, mainstream Filipino cinema still favors the effeminate gay.
Thesis -- Bachelor of Arts in Communication and Media Studies. University of the Philippines Visayas, Miagao, Iloilo.
Keywords: Gay-themed film; Philippine cinema; Portrayal -- Gay character; Masculine; Effeminate gay; Comedy -- Film; Performance -- Gay character